Vowel and Diphthongs Error Analysis of Random Secondary Students of Semarang - Fransiska Marsela Hambur (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
Second language acquisition can be a significant issue which leads to the study of language transfer and interference. Since there are many problems faced regarding pronunciation, then this paper is aimed at revealing and describing the errors in pronouncing English sounds made by the Javanese native speaker secondary students who learn English as their second language. Vowels and diphthongs pronunciations are examined closely in this study. Mix method was used started by the qualitative one and quantitative one to know the percentage of each data. The source of the data was some recording of students’ interview and then it was transcribed into broad transcription without suprasegmental features. In analysis, the distinctive features are applied to establish phonological patterns of pronunciation errors. The results of this study revealed that Javanese Native Speaker made some errors in pronouncing English sounds, especially in diphthongs case in which all speakers experience phonetic interferences: substitution and underdifferenciation.